Security and Forensic Analysis for Industrial Ethernet Protocols - Yu, Geon; Shon, Taeshik (2022 International Conference on Platform Technology and Service, PlatCon 2022 - Proceedings, 2022)
As the era of the 4th Industrial Revolution has begun, the industrial Ethernet share of smart factories increased significantly as the compatibility of protocols, which are problems with existing field buses, improved. However, as the share of the Industrial Ethernet has increased, security concerns have also increased. In this paper, we explore security issues, anomaly detection, and network forensics technologies that may arise after analysis for the Industrial Ethernet protocols such as Ethernet/IP, PROFINET, CC-Link/IE, and RAPIEnet, etc. Through the previous analysis, we propose about the security issues that must be carried out in the Industrial Ethernet Protocol in the future.
Keywords: Ethernet protocols; Fieldbus; Forensic analysis; Industrial ethernet protocol; Industrial Ethernets; Industrial revolutions; IS problems; Security; Security analysis; Security issues; Industrial Ethernet Protocol; Network Forensic; Security